2014
DOI: 10.1175/jpo-d-13-0159.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Patterns of Mesoscale Eddy Properties and Diffusivities

Abstract: Mesoscale eddies play a major role in the transport of tracers in the ocean. Focusing on a sector in the east Pacific, the authors present estimates of eddy diffusivities derived from kinematic tracer simulations using satellite-observed velocity fields. Meridional diffusivities are diagnosed, and how they are related to eddy properties through the mixing length formulation of Ferrari and Nikurashin, which accounts for the suppression of diffusivity due to eddy propagation relative to the mean flow, is shown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
211
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(237 citation statements)
references
References 64 publications
(100 reference statements)
25
211
1
Order By: Relevance
“…A number of diffusivity estimates other than Okubo's have been made for the Gulf Stream extension region (e.g., Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012;Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;or Cole et al, 2015). These estimates are based on surface drifters (Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012), satellite-observed velocity fields (Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;Rypina et al, 2012), and Argo float observations (Cole et al, 2015), and they use either the spread of drifters or the evolution of simulated or observed tracer fields to deduce diffusivity.…”
Section: Application To the Altimetric Velocities In The Gulfmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of diffusivity estimates other than Okubo's have been made for the Gulf Stream extension region (e.g., Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012;Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;or Cole et al, 2015). These estimates are based on surface drifters (Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012), satellite-observed velocity fields (Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;Rypina et al, 2012), and Argo float observations (Cole et al, 2015), and they use either the spread of drifters or the evolution of simulated or observed tracer fields to deduce diffusivity.…”
Section: Application To the Altimetric Velocities In The Gulfmentioning
confidence: 99%
“…These estimates are based on surface drifters (Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012), satellite-observed velocity fields (Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;Rypina et al, 2012), and Argo float observations (Cole et al, 2015), and they use either the spread of drifters or the evolution of simulated or observed tracer fields to deduce diffusivity. The resulting diffusivities are spatially varying and span 2 orders of magnitude, from 2 × 10 4 m 2 s −1 in the most energetic regions in the immediate vicinity of the Gulf Stream and its extension, to 10 3 m 2 s −1 in less energetic areas, to 200 m 2 s −1 in the coastal areas of the Slope Sea.…”
Section: Application To the Altimetric Velocities In The Gulfmentioning
confidence: 99%
See 1 more Smart Citation
“…Their structure and energy vary widely over the global ocean, [9][10][11][12] and recent studies have suggested that mesoscale eddy energy transport may play a significant role in setting the large scale distribution of mesoscale eddy energy. 19,20,22 In long-running global climate models, these eddies are not resolved, and mesoscale eddy energy transport is not taken into account in most parameterizations of their effects.…”
Section: -6 Ian Groomsmentioning
confidence: 99%
“…Several parameterizations of κ GM are of the form κ GM ∝ ℓ 2 /T or κ GM ∝ V ℓ where V , ℓ, and T are velocity, length, and time scales of the eddies that are given as functions of the resolved large scale flow. 7,8 The characteristic length, time, and velocity scales of mesoscale eddies vary considerably over the global ocean, [9][10][11][12] and any successful model for κ GM should reflect this. In a recent diagnostic study of the effects of mesoscale eddies in an idealized channel simulation Bachman and Fox-Kemper 3 found that it was possible to construct a very accurate model of the form κ GM ∝ V ℓ provided that V was diagnosed directly from an eddy-resolving simulation, whereas available predictions of V based only on local properties of the large-scale flow were inaccurate.…”
mentioning
confidence: 99%